Bubbles and financial professionals - Utz Weitzel; Christoph Huber; Florian Lindner; Jürgen Huber; Julia Rose; Michael Kirchler (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2018)
The efficiency of financial markets and their potential to produce bubbles are central topics in academic and professional debates. Yet, surprisingly little is known about the contribution of financial professionals to price efficiency. To close this gap, we run 86 experimental markets with 294 professionals and 384 students. We report that professional markets with bubble-drivers-capital inflows or high initial capital supply-are susceptible to bubbles, but they are significantly more efficient than student markets. In a survey with 245 professionals and students we show that cognitive skills and risk attitudes do not explain subject pool differences in bubble formation.
Keywords: C92; D84; G02; G14; 330; experimental finance; financial professionals; price efficiency; financial bubbles